Implementasi Pendidikan Berbasis Budaya Sunda di SMPN 5 Lembang - Desi Lia Aprilaini; Indira Aristianti; Trias Komala Desmayanti; Rima Irmayanti (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research aims to gain an understanding of the events or phenomena that occur within the context of the community, particularly in the context of Sundanese culture-based education. The research adopts a qualitative research method and is conducted at SMPN 5 Lembang. The research findings indicate several points: (1) The students at SMPN 5 Lembang show great enthusiasm towards Sundanese culture. (2) The Sundanese language is widely used in the school. (3) There is an implementation of guidance and counseling based on Sundanese culture at SMPN 5 Lembang.